Protective Effect of Apocynin in a Mouse Model of Chemically-Induced Colitis - Marín, Marta; Giner, Rosa María; Ríos, José-Luis; Recio, María del Carmen (Planta Medica, 2013)
Apocynin, a constituent of Picrorhiza kurroa, successfully inhibits NADPH oxidase and shows promise as an anti-inflammatory drug. Now, we report anti-inflammatory effects of apocynin in an experimental colitis model induced by dextran sulfate sodium as well as the effects on the mediators involved in this process. Apocynin reduced the colitis induced in mice by administration of 5 % dextran sulfate sodium during 7 days. Mice were fed a control diet or a diet supplemented with 2 % of apocynin or 2 % of rutin. Sulfasalazine (50 mg/kg, p. o.) was used as a positive control. Treatment with apocynin and rutin ameliorated the course of colonic inflammation with results similar to those of the reference drug, as could be seen by reductions in the disease activity index scores and colon length. NO and PGE2 production as well as the iNOS and COX-2 expression were reduced by apocynin and rutin. Moreover, the activation of NF-κB p65 as well as STAT3 in dextran sulfate sodium-treated colon tissues was significantly reduced by apocynin. These results are promising for further experimental studies on treating gastrointestinal diseases and on the potential protective effects of apocynin.
Keywords: apocynin; dextran sulfate sodium; inflammatory bowel disease; ulcerative colitis; inflammatory cytokines; Picrorhiza kurroa; Scrophulariaceae